2017
DOI: 10.1097/md.0000000000008701
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Bacillus cereus endophthalmitis with endoscopy-assisted vitrectomy

Abstract: To evaluate the use of endoscopy-assisted vitrectomy in patients with sight-threatening Bacillus cereus endophthalmitis.A retrospective analysis was conducted in 15 eyes with Bacillus cereus endophthalmitis. Patients were divided into 2 groups: endoscopy-assisted vitrectomy (5 eyes) and conventional vitrectomy (10 eyes). The following clinical data were recorded and analyzed: sex, age, latent period, symptom duration, follow-up time, visual acuity pre- and postsurgery, recurrence of endophthalmitis, incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…Previous reports have shown that posttraumatic Bacillus cereus endophthalmitis can cause complete corneal opacification within 24 hours of injury [ 32 ]. Pan et al recommended endoscopy-assisted vitrectomy as an alternative treatment for Bacillus cereus endophthalmitis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that posttraumatic Bacillus cereus endophthalmitis can cause complete corneal opacification within 24 hours of injury [ 32 ]. Pan et al recommended endoscopy-assisted vitrectomy as an alternative treatment for Bacillus cereus endophthalmitis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, vitrectomy has been used to treat Bacillus cereus endophthalmitis. For example, Pan et al reported 15 patients with Bacillus cereus endophthalmitis treated by vitrectomy with or without endoscopy assistance; however, four of them underwent enucleation [ 24 ]. There is no doubt that early application of sensitive antibiotics is helpful in controlling infections.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of endoscopy in cases of media opacity are well established (endophthalmitis, trauma); [19][20][21][22][23] nonetheless, a broader number of indications for endoscopy exists when used as "endoscopy-assisted" vitrectomy. 6,18,[24][25][26][27][28][29] We propose the use of endoscopy to perform a detailed endoscopic revision during SO extraction in complex RDs.…”
Section: Discussionmentioning
confidence: 99%
“…( C ) A patient with post-operative E. faecalis endophthalmitis presents with exudative membrane and infiltrates, ocular injection, and a hypopyon. This figure is reproduced under a Creative Commons Attribution-NonCommercial-ShareAlike License from © 2019 Indian Journal of Ophthalmology [158], the Creative Commons Attribution-ShareAlike License 4.0 from © 2017 Medicine [159], and the Creative Commons Attribution-NonCommercial 3.0 Unported from © 2015 J Korean Ophthalmol Soc [160].…”
Section: Figurementioning
confidence: 99%